STRATEGIC APPROPRIATION ON HUSTLE CULTURE AS POSITIVE TREND - Muhammad Agung Budiarjo; Roma Ulinnuha (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
Hustle culture is a cultural phenomenon that was born outside and was adopted in Indonesia as a continuous culture of workaholism. Hustle also plays an important role at work, because hustle is a new movement for workers to commit to their company. Hustle can also be categorized as good behavior. Because workers give their full role and work optimall y. In Indonesia, this culture continues to develop, especially the millennial generation of teenagers. It is easier for them to work hard, even to generate fantasy income. They adopt workaholic behavior to become financially successful. There are many rejections and disagreements between researchers regarding this Hustle culture. research data is a mix of methods by combining qualitative research and literature review which contains searches of relevant concepts and theories using research objectives. By involving a combination of fieldwork, social media observations, and interviews. The purpose of this literature and field study is to describe hustle culture in Indonesia as a positive trend for teenagers in Indonesia.